Developments in soluble lead flow batteries and remaining challenges: An illustrated review. (February 2018) - Krishna, M.; Fraser, E.J.; Wills, R.G.A.; Walsh, F.C.
Highlights: A brief history of lead-based batteries with an emphasis on the development of the soluble lead flow battery (SLFB) is presented. All SLFB publications to date are reviewed, providing a comprehensive introduction to SLFB research, the developments and remaining challenges. Experience from the lead-acid battery and lead dioxide coatings industry is applied to better understand the observations made in SLFB research. Scalability of the system is considered, involving a description of the 1000 cm 2 flow cell stack only available as a DTI technical report. Abstract: The soluble-lead flow battery (SLFB) utilises methanesulfonic acid, an electrolyte in which Pb(II) ions are highly soluble. During charge, solid lead and lead dioxide layers are electrodeposited at the negative and positive electrodes respectively. During discharge, the deposits are electrochemically dissolved back into the recirculating electrolyte. The cell is normally undivided, which greatly reduces design complexity and cost, whilst also reducing the flow pumping requirements. Typical SLFB electrolytes offer up to 40 W h kg −1 of storage, with performance on the 100 cm 2 electrode scale reaching 90% charge and 80% voltage efficiencies across 100 cycles; however, the SLFB has also been tested on the 1000 cm 2 electrode, four-cell stack scale. This review considers the SLFB, highlighting important developments and discussing remaining problems. In particular, methods to achieve effective stripping of lead dioxide at the positive electrode and to prevent lead dendrites at the negative electrode in order to prevent contact between the deposits, and thus shorting, are explored. A detailed understanding of the effect of Pb(II) and methanesulfonic acid concentration on the physical electrolyte properties is presented, and possible improvements to the electrodes and electrolyte composition in terms of additives are discussed in order to improve cell efficiency and longevity. Also, the importance of cell design in preventing the failure mechanisms and therefore achieving a high performance is highlighted. Studies on mathematical modelling and cycling simulation are also reviewed. Continuing research needs are listed and a forward look to future developments is taken.